2021
DOI: 10.1212/wnl.0000000000011742
|View full text |Cite
|
Sign up to set email alerts
|

Blood Biomarkers to Differentiate Ischemic and Hemorrhagic Strokes

Abstract: Objective:We aimed to validate a panel of blood biomarkers to differentiate between ischemic stroke (IS) and intracerebral hemorrhage (ICH) in patients with suspected stroke.Methods:Patients with suspected stroke admitted within 4.5 hours after onset were enrolled. Blood samples were collected at hospital admission. Glial fibrillary acid protein (GFAP), retinol binding protein 4 (RBP-4), N-terminal pro B-type natriuretic peptide (NT-proBNP) and endostatin were measured by immunoassays. Cut-off points were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 24 publications
1
61
0
3
Order By: Relevance
“…Additionally, within 4 and 6 h after symptom onset, serum GFAP had an AUC of 0.866 for differentiating HS from IS and SM, with a sensitivity of 75.0% and specificity of 84.0% using an optimal cutoff point of 72 ng/l ( 14 ); another study reported an AUC of 0.872 with a sensitivity of 77.8% and specificity of 94.2% using a cutoff of 0.03 μg/l within 6 h after symptom onset ( 22 ). A recent clinical study reported that plasma GFAP within 4.5 h after symptom onset was higher in HS patients than in IS patients ( 23 ).…”
Section: Biomarkers Associated With Glial Activationmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, within 4 and 6 h after symptom onset, serum GFAP had an AUC of 0.866 for differentiating HS from IS and SM, with a sensitivity of 75.0% and specificity of 84.0% using an optimal cutoff point of 72 ng/l ( 14 ); another study reported an AUC of 0.872 with a sensitivity of 77.8% and specificity of 94.2% using a cutoff of 0.03 μg/l within 6 h after symptom onset ( 22 ). A recent clinical study reported that plasma GFAP within 4.5 h after symptom onset was higher in HS patients than in IS patients ( 23 ).…”
Section: Biomarkers Associated With Glial Activationmentioning
confidence: 99%
“…Moreover, the combination of RPB4 and GFAP improved the detection of IS ( 46 ). A recent clinical study reported that plasma RBP4 within 4.5 h after symptom onset was higher in IS patients than in HS patients ( 23 ).…”
Section: Biomarkers Associated With Inflammation and Oxidative Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…A strategy to improve stroke differential diagnosis (stroke vs. non-stroke) and type of stroke (IS vs. HS) can be achieved by including additional biomarkers to the current practice that include clinical and neuroimaging characteristics. In fact, recent studies have highlighted the potential of blood-derived biomarkers for timely patient triage, therapeutics, and in revealing stroke mechanisms [ 26 , 27 ]. Easily accessible fluid biomarkers can provide an objective evaluation of the real-time panorama, supporting stroke diagnosis or predicting the patient’s outcome, ultimately guiding clinical decisions [ 11 , 13 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%